2020
DOI: 10.1038/s41467-020-18285-z
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and oxygen-release driven delithiation in Li2MnO3

Abstract: Lithium-excess layered cathode materials such as Li2MnO3 have attracted much attention owing to their high energy densities. It has been proposed that oxygen-release and cation-mixing might be induced by delithiation. However, it is still unclear as to how the delithiated-region grows. Here, by using atomic-resolution scanning transmission electron microscopy combined with electron energy-loss spectroscopy, we directly observe the atomic structures at the interface between pristine and delithiated regions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 38 publications
(48 reference statements)
1
33
0
Order By: Relevance
“…Figure 1j displays a deeper view of the Mn EELS by testing the L 3 /L 2 ratio of Mn L 2 , 3 edges, which are sensitive to Mn valence. [ 35 ] The L 3 /L 2 ratio in the range of 3–5 nm is larger than that in the range of 6–15 nm, indicating a lower valence of Mn in the surface spinel structure with a 5 nm‐thick shell than that in the bulk layered phase.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1j displays a deeper view of the Mn EELS by testing the L 3 /L 2 ratio of Mn L 2 , 3 edges, which are sensitive to Mn valence. [ 35 ] The L 3 /L 2 ratio in the range of 3–5 nm is larger than that in the range of 6–15 nm, indicating a lower valence of Mn in the surface spinel structure with a 5 nm‐thick shell than that in the bulk layered phase.…”
Section: Resultsmentioning
confidence: 99%
“…6A], it is found that the slope below 4.4 V during charging corresponds to the charge compensation of Ni 2+ /Ni 4+ and Co 3+ /Co 4+ without the variation of the Mn 4+ valence, which is attributed to the charge compensation mechanism of the LiMO 2 component [9] . The absorption edge of the TM at 4.5 V shows that there is no change in the K edge of Ni and Co [81] . The Mn K-edge X-ray absorption near-edge structure spectrum indicates that the environment of Mn changes at 4.5 V according to the continuous variation of the absorption edge, which results from the distortion of MnO 6 octahedra.…”
Section: Charge Compensation Mechanismmentioning
confidence: 94%
“…So far, the state-of-the-art characterization techniques have provided multiscale structure and spectroscopy information to understand the structure evolution of LLOs. It is now believed that a series of disordered structures generated, such as lattice distortion, dislocation, and stacking faults, disturb the structure stability. ,, Some unusual ways are proposed to suppress structures degradation effectively. Embedding the undesired disordered structures into pristine host structures is favored to promote the structure stability. Our recent work further illustrates that subtle adjustments of the disordered structures from type/range/distribution are necessary to mobilize them as a modification method .…”
mentioning
confidence: 99%
“…8−12 It is now believed that a series of disordered structures generated, such as lattice distortion, dislocation, and stacking faults, disturb the structure stability. 10,11,13 Some unusual ways are proposed to suppress structures degradation effectively. Embedding the undesired disordered structures into pristine host structures is favored to promote the structure stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation